GmMYB181, a Soybean R2R3-MYB Protein, Increases Branch Number in Transgenic Arabidopsis - Yang, Hui; Xue, Qian; Zhang, Zhenzhen; Du, Jingyi; Yu, Deyue; Huang, Fang (Frontiers in Plant Science, 2018)
Soybean (Glycine max) is an important economic crop that provides abundant oil and high quality protein for human beings. As the process of reproductive growth directly determines the crop seed yield and quality, we initiated studies to identify genes that regulate soybean floral organ development. One R2R3-MYB transcription factor gene, designated as GmMYB181, was found to be enriched in flowers based on microarray analysis and was further functionally investigated in transgenic Arabidopsis. GmMYB181 protein contains two MYB domains, which localized to the nucleus and displayed transcriptional activation in yeast hybrid system. Real-time quantitative PCR (qRT-PCR) results suggested GmMYB181 exclusively expressed in flower tissue. In Arabidopsis, overexpression of GmMYB181 altered the morphology of floral organs, fruit size and plant architecture, including outward curly sepals, smaller siliques, increased lateral branches and reduced plant height, indicating that GmMYB181 is involved in the development of reproductive organs and plays an important role in controlling plant architecture. Further, microarray analysis revealed that overexpressing GmMYB181 in Arabidopsis affected the expression of 3450 genes in mature flowers, including those involved in floral organ, seed/fruit development, and responded to different hormone signals.